Toward a multi-causal model of successful conflict regulation through territorial self-government: lessons from South Tyrol - Schulte, Felix (Austrian journal of political science, 2019)
Territorial autonomies have been increasingly implemented as tools for the regulation of ethnic self-determination conflicts. Recent literature has primarily focused on the debate about the general conflict-solving potential of territorial self-government in multi-ethnic societies. However, autonomy consolidation is not an entirely endogenous process, but affected by various structural and actor-centered factors. Previous studies have so far given unsatisfactory answers as to the conditions under which reforms of autonomy succeed or fail in post-conflict situations. Building on Social Identity Theory, it is argued that ethnic recognition is the all-important condition for autonomy consolidation, which, however, presupposes specific, favorable framework conditions. A high scope of transferred competencies, weak horizontal inequalities, democratic-inclusive institutions, minority-friendly parties, and international engagement are identified as pivotal factors supporting the process of mutual recognition between ethnic groups. To test our theoretical assumptions, we create a multi-causal process model. We find evidence for the proposed mechanisms in a process-tracing case study on South Tyrols successful autonomy consolidation.